ECOLOGICAL INNOVATIONS AS A DRIVER OF SUSTAINABLE DEVELOPMENT IN BUSINESS - Zabarna, Eleonora; Chernenko, Evgeniya; Cherepanova, N.O. (Sworld-Us Conference proceedings, 2025)
The paper provides a definition of eco-innovations and presents their main features. It is proven that environmental innovations can become the basis for creating new markets and business models. It is shown that digital communication tools, in particular